Association of socioeconomic status with glycated haemoglobin level and risk factors for diabetic retinopathy: a cross-sectional study in Sichuan, western China. Issue 2 (16th February 2023) - Xu, Xinyin; Yang, Wei; Deng, Yin; Liu, Lingling; Zhang, Xin; Long, Chengxu; Dong, Ting; Zeng, Jing; Kui, Ji; Wu, Xianping
Abstract : Objective: Diabetes affects 1 in 10 adults in China. Diabetic retinopathy (DR) is a diabetes-related complication that, if untreated, impairs vision and causes blindness. Evidence on DR diagnosis and risk factors is limited. This study aimed to add evidence from socioeconomic factors. Design: A cross-sectional survey of people with diabetes conducted in 2019 was analysed by using logistic regression to evaluate the association of socioeconomic factors with the glycated haemoglobin (HbA1c) level and DR. Setting: Five counties/districts of western China (Sichuan) were included. Participants: Registered participants with diabetes aged from 18 to 75 years were selected, and at last 2179 participants were included in the analysis. Results: In this cohort, 37.13% (adjusted value 36.52%), 19.78% (adjusted value 19.59%) and 17.37% of participants had HbA1c<7.0%, DR (24.96% of those in the high-HbA1c group) and non-proliferative DR, respectively. Participants with higher social health insurance coverage (urban employee insurance (UEI)), higher income and urban residents tended to have glycaemic control (HbA1c) compared with their counterparts (OR: 1.48, 1.08 and 1.39, respectively). Participants with UEI or higher income had a lower risk of DR (OR: 0.71 and 0.88, respectively); higher education was associated with a 53%–69% decreased risk of DR. Conclusion: This study shows disparities in the effect of socioeconomic factors on glycaemic (HbA1c) management and DR diagnosis among people with diabetes in Sichuan. Lower socioeconomic (especially non-UEI) status conferred a higher risk of high HbA1c and DR. The insights from this study indicate the need for national programmes to implement community-level measures to facilitate access to better HbA1c management and early detection of DR in patients with lower socioeconomic status and diabetes. Trial registration number: Chinese Clinical Trial Registry (ChiCTR1800014432).